The effects of hesperidin supplementation on cardiovascular risk factors in adults: a systematic review and dose–response meta-analysis - Khorasanian, Atie Sadat; Fateh, Sahand Tehrani; Gholami, Fatemeh; Rasaei, Niloufar; Gerami, Hadis; Khayyatzadeh, Sayyed Saeid; Shiraseb, Farideh; Asbaghi, Omid (Frontiers in Nutrition, 2023)
Hesperidin is a natural-based bioactive compound with possible metabolic effects that have an inconclusive potential role in the risks of cardiovascular disease. Consequently, the present study aimed to examine the effects of hesperidin supplementation on cardiovascular risk factors in adults. A systematic search up to August 2022 on all randomized controlled trials (RCTs) in Scopus, PubMed, Embase database, Cochrane Library, and ISI Web of Science databases using pertinent keywords were completed. Weighted mean difference (WMD) and 95% confidence intervals (CIs) were calculated via a random-effects model. Pooled analysis demonstrated significant decreases in serum triglyceride (TG) (WMD=-13.85 mg/dl, 95%CI:-27.21, -0.49; P=0.042), total cholesterol (TC) (WMD=-5.42 mg/dl, 95%CI:-10.10, -0.75; P=0.023), low-density cholesterol (LDL) (WMD=-5.29 mg/dl, 95%CI:-9.63, -0.95; P=0.017), tumor necrosis factor-alpha (TNF-α) (WMD=-2.74 pg/ml; 95%CI:-4.89, -0.60; P=0.012), systolic blood pressure (SBP) (WMD=-1.37mmHg; 95%CI:-2.73, -0.02; P=0.046), a significant increase in weight (WMD=0.09 kg; 95%CI: 0.06, 0.13, P<0.001) and no significant effect on high-density cholesterol (HDL) (P=0.157), waist circumference (WC) (P=0.051) fasting blood glucose (FBG) (P=0.11), insulin (P=0.145), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (P=0.180), C-reactive protein (CRP) (P=0.560), interlukin-6 (IL-6) (P=0.121), body mass index (BMI) (P=0.35), and diastolic blood pressure (DBP) (P=0.415). Moreover, the nonlinear dose-response analysis detected, the effective dosage of hesperidin supplementation to be about 1000 mg/d and a more effective duration of>8 weeks causing a decrease in insulin levels and also, and the duration of the intervention of more than six weeks be effective to the decrement of FBG.